Bacterial growth inhibitory activity for nanostructured copper minerals obtained from the Marañon region: comparison with commercial copper - Sánchez-Venegas, Jaime (2016)
In this paper, we report on the bacterial growth inhibitory activity of nanoparticles of cemented and commercial copper. Strains of Staphylococcus aureus ATCC 6538 (Gram positive) and Escherichia coli ATCC 35218 (Gram negative) were used to determine the inhibitory effect by the minimal inhibitory concentration of the nanoparticles diluted in nutrient culture broth and distributed in ELISA plates. The copper cements (obtained from hydrometallurgical processes) and the commercial one were nanostructured employing a mechanical milling equipment. The results indicate that commercial copper nanoparticles (after 2.5 hours of milling) show growth inhibitory action of S. aureus strain. However, in the case of E. coli strains no inhibitory action has been observed. It was also determined that the minimal inhibitory concentration of the commercial copper is 20 μg/mL against S. aureus. On the other hand, copper cements (in solid and nanostructured form) do not show inhibitory effects.